2022
DOI: 10.3389/fphar.2022.865389
|View full text |Cite
|
Sign up to set email alerts
|

ASPP2 Coordinates ERS-Mediated Autophagy and Apoptosis Through mTORC1 Pathway in Hepatocyte Injury Induced by TNF-α

Abstract: Background: Though ASPP2 plays an important role in regulating cell apoptosis and autophagy in case of liver injury, there remains a lack of clarity on the molecular mechanism of ASPP2 regulating autophagy and apoptosis.Methods: A hepatocyte injury model was constructed using HL7702 cell line and TNF-α. The cells were treated by ASPP2 overexpression adenovirus or short hairpin RNA lentivirus and endoplasmic reticulum stress (ERS) or the mammalian target of rapamycin (mTOR) inhibitor or agonist, respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Numerous studies have shown that mTOR plays an important role in lipid metabolism 25,26 . Our previous study found that ASPP2 can mediate the mTOR signaling pathway to regulate autophagy 13 . In this study, we found that ethanol-fed WT mice caused signi cant liver steatosis and liver injury, while deletion of hepatic ASPP2 effectively alleviated lipid accumulation in the liver and suppressed the levels of AST, ALT, TC, and TG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that mTOR plays an important role in lipid metabolism 25,26 . Our previous study found that ASPP2 can mediate the mTOR signaling pathway to regulate autophagy 13 . In this study, we found that ethanol-fed WT mice caused signi cant liver steatosis and liver injury, while deletion of hepatic ASPP2 effectively alleviated lipid accumulation in the liver and suppressed the levels of AST, ALT, TC, and TG.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that ASPP2 can participate in the regulation of the mammalian target of rapamycin complex 1 (mTORC1) signaling pathway 13 . Research has shown that mTORC1 plays an important role in lipid metabolism 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The data presented in this study indicate that GRb1 may have a protective effect against hepatotoxicity induced by CTD, potentially through its ability to reduce apoptosis, which validated the results of network prediction. Research has reported that apoptosis may be induced due to excess ERS 36 . A growing body of evidence has substantiated that in ERS conditions, the accumulation of unfolded or misfolded proteins occurs within the cellular ER, resulting in apoptosis and ultimately contributing to hepatotoxicity 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Research has reported that apoptosis may be induced due to excess ERS. 36 A growing body of evidence has substantiated that in ERS conditions, the accumulation of unfolded or misfolded proteins occurs within the cellular ER, resulting in apoptosis and ultimately contributing to hepatotoxicity. 37 There is evidence that ERS participates in the occurrence and development of various liver disorders, including fatty liver, ischemia-reperfusion injury, liver fibrosis and DILI.…”
Section: Integrated Network Analysis To Elucidate the Protective Mech...mentioning
confidence: 99%
“…The enhanced autophagy activity can promote the conversion of long-chain acyl-CoA molecule to acetyl-CoA molecule by increasing fatty acid beta-oxidation, furthermore, leading to the breakdown of long chain fatty acids (50). Overexpression of ASPP2 significantly reduced the activity of autophagy in both HepG2 cells and BALB/c mice, while ASPP2 silencing induced autophagic flux through increasing the conversion of LC3I to LC3II (29,51). Thus, the effect of APSS2 on long-chain fatty acids that we found in the present study is likely due to the activation of autophagy-related lipid metabolic pathways in ASPP2 +/mice.…”
Section: Discussionmentioning
confidence: 99%